Derivative of Log X

A function defined by y = {\log _a}x,\,\,\,x > 0, where x = {a^y},\,\,\,a > 0, a \ne 1 is called the logarithm of x to the base a. The common logarithmic function is written as y = {\log _{10}}x.

We shall prove formula for derivative of natural logarithm function using by definition or first principle method.

Let us suppose that the function of the form

y = f\left( x \right) =  {\log _a}x

First we take the increment or small change in the function.

\begin{gathered} y + \Delta y = {\log _a}\left( {x + \Delta x}  \right) \\ \Delta y = {\log _a}\left( {x + \Delta x}  \right) - y \\ \end{gathered}

Putting the value of function y = {\log _a}x in the above equation, we get

\begin{gathered} \Delta y = {\log _a}\left( {x + \Delta x}  \right) - {\log _a}x \\ \Delta y = {\log _a}\left( {\frac{{x + \Delta  x}}{x}} \right) \\ \Delta y = {\log _a}\left( {1 + \frac{{\Delta  x}}{x}} \right) \\ \end{gathered}

Dividing both sides by \Delta  x, we get

\frac{{\Delta  y}}{{\Delta x}} = \frac{1}{{\Delta x}}{\log _a}\left( {1 + \frac{{\Delta  x}}{x}} \right)

Multiplying and dividing the right hand side by x, we have

\begin{gathered} \Rightarrow \frac{{\Delta y}}{{\Delta x}} =  \frac{1}{x}\frac{x}{{\Delta x}}{\log _a}\left( {1 + \frac{{\Delta x}}{x}}  \right) \\ \Rightarrow \frac{{\Delta y}}{{\Delta x}} =  \frac{1}{x}{\log _a}{\left( {1 + \frac{{\Delta x}}{x}}  \right)^{\frac{x}{{\Delta x}}}} \\ \end{gathered}

Taking limit of both sides as \Delta x \to 0, we have

\begin{gathered} \Rightarrow \mathop {\lim }\limits_{\Delta x  \to 0} \frac{{\Delta y}}{{\Delta x}} = \mathop {\lim }\limits_{\Delta x \to 0}  \frac{1}{x}{\log _a}{\left( {1 + \frac{{\Delta x}}{x}}  \right)^{\frac{x}{{\Delta x}}}} \\ \Rightarrow \mathop {\lim }\limits_{\Delta x  \to 0} \frac{{\Delta y}}{{\Delta x}} = \frac{1}{x}\mathop {\lim  }\limits_{\Delta x \to 0} {\log _a}{\left( {1 + \frac{{\Delta x}}{x}}  \right)^{\frac{x}{{\Delta x}}}} \\ \end{gathered}

Consider \frac{{\Delta  x}}{x} = u \Rightarrow \frac{x}{{\Delta x}} = \frac{1}{u}, as \Delta x \to 0 then u \to 0, we get

  \Rightarrow \frac{{dy}}{{dx}} = \frac{1}{x}\mathop {\lim }\limits_{u \to 0}  {\log _a}{\left( {1 + u} \right)^{\frac{1}{u}}}

Using the relation from limit \mathop {\lim }\limits_{x \to 0} {\left( {1 + x}  \right)^{\frac{1}{x}}} = e, we have

\begin{gathered} \frac{{dy}}{{dx}} = \frac{1}{x}{\log  _a}\left( e \right) \\ \Rightarrow \frac{{dy}}{{dx}} =  \frac{1}{{x\ln a}} \\ \Rightarrow \frac{d}{{dx}}\left( {{{\log  }_a}x} \right) = \frac{1}{{x\ln a}} \\ \end{gathered}

Example: Find the derivative of

y = f\left( x \right)  = {\log _{10}}{x^2}

We have the given function as

y =  {\log _{10}}{x^2}

Differentiation with respect to variable x, we get

\frac{{dy}}{{dx}}  = \frac{d}{{dx}}{\log _{10}}{x^2}

Using the rule, \frac{d}{{dx}}\left(  {{{\log }_a}x} \right) = \frac{1}{{x\ln a}}, we get

\begin{gathered} \frac{{dy}}{{dx}} = \frac{1}{{{x^2}\ln  10}}\frac{d}{{dx}}\left( {{x^2}} \right) \\ \Rightarrow \frac{{dy}}{{dx}} =  \frac{{2x}}{{{x^2}\ln 10}} \\ \Rightarrow \frac{{dy}}{{dx}} =  \frac{2}{{x\ln 10}} \\ \end{gathered}